2020
DOI: 10.1186/s12967-020-02636-x
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in liver metastasis: its clinical significance and discordance with primary tumor in colorectal cancer

Abstract: Background The outcomes of immune checkpoint inhibitors in cancer patients with liver metastases are poor, which may be related to a different tumor microenvironment in liver metastases from primary tumors. This study was aimed to analyze PD-L1 expression and the immune microenvironment status in liver metastases and compare the differences of PD-L1 expression between primary tumors and liver metastases of colorectal cancer. Methods 74 cases of pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…However, this mechanism is utilized by cancers to escape from anti-tumor immunity. Previous study showed that the expression of PD-L1 was increased in liver metastases compared to primary CRC, indicating different intrinsic microenvironment between primary and metastatic CRC [ 110 ], which may help CRC liver metastases escape from immune surveillance. In addition, it was reported that chemotherapy can modulate PD-L1 and TIM-3 expression in CRC liver metastases, suggesting the potential strategy of combined chemo-immunotherapies [ 111 ].…”
Section: Liver Immune Microenvironment For Crc Liver Metastasismentioning
confidence: 99%
“…However, this mechanism is utilized by cancers to escape from anti-tumor immunity. Previous study showed that the expression of PD-L1 was increased in liver metastases compared to primary CRC, indicating different intrinsic microenvironment between primary and metastatic CRC [ 110 ], which may help CRC liver metastases escape from immune surveillance. In addition, it was reported that chemotherapy can modulate PD-L1 and TIM-3 expression in CRC liver metastases, suggesting the potential strategy of combined chemo-immunotherapies [ 111 ].…”
Section: Liver Immune Microenvironment For Crc Liver Metastasismentioning
confidence: 99%
“…Some studies showed that high PD-L1 expression was associated with tumor metastasis, cancer recurrence, and tumor invasion; PD-L1 could be considered an independent element in evaluating immunotherapy during metastasis [ 27 , 28 ]. As such, PD-L1 could play a crucial role in the immune microenvironment between the primary tumor and the secondary metastatic tumor; PD-L1 can help increase the understanding of cancer’s response to immunotherapy and develop PD-L-targeted therapy [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry staining of tissue sections was performed as described previously. 23 An antihuman PD-L1 monoclonal antibody (E1L3N, Cell Signaling Technology) was used per the manufacturer’s instructions. PD-L1 expression was evaluated using the scoring method of the combined positive score (CPS), which is the number of positive cells (tumor cells, lymphocytes, and macrophages)/the total number of viable tumor cells, and multiplied by 100.…”
Section: Methodsmentioning
confidence: 99%